"The liberation of LGBTQ+ will also liberate heterosexuals": Heterosexual feminist women's participation in solidarity‐based collective action for LGBTQ+ rights. (21st February 2022) - Uysal, Mete Sefa; Uluğ, Özden Melis; Kanık, Betül; Aydemir, Aslı
Abstract: The current studies aim to examine the underlying predictors of heterosexual feminist women's willingness to participate in solidarity‐based collective action for LGBTQ+ rights. We hypothesized that feminist identification, perceived discrimination against LGBTQ+, and strategic intra‐minority alliance between feminists and LGBTQ+ would predict their willingness to participate in solidarity‐based collective action. Study 1 ( N = 141) showed that higher feminist identification and more endorsement of the strategic intra‐minority alliance predicted more willingness to participate in solidarity‐based collective action among heterosexual feminist women in Turkey. Study 2 ( N = 644) replicated and extended the findings of Study 1 with a larger sample by showing that higher awareness of sexual orientation privilege predicts more willingness to participate in solidarity‐based collective action. By following an intersectional and multi‐identity approach in Study 3 ( N = 280), we showed that higher feminist identification predicted more willingness to participate in solidarity‐based collective action, whereas higher heterosexual identification predicted less willingness.